2022
DOI: 10.18502/jri.v23i3.10006
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1, Dopamine, and NADPH levels in Infertile Women with Polycystic Ovary Syndrome: Is There a Relationship Between Their Levels and Metabolic and Hormonal Variables

Abstract: Background: Polycystic ovary syndrome (PCOS) is commonest endocrine disease occurring in women of reproductive age. This study conducted to clarify altered concentrations of Nesfatin-1, nicotinamide adenine dinucleotide phosphate (NADPH), and dopamine in PCOS women and controls. Also, to assess their role in PCOS pathophysiology and their correlation with measured biochemical parameters. Methods: In this observational study, 60 PCOS patients and 24 controls included. Medical history was recorded and full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
2
11
1
Order By: Relevance
“…There is a strong correlation between PCOS with obesity, especially central obesity, as reported by previously conducted studies [26,27]. Similar results were reported by Abdelazim et al [28], who found that 35.5% of PCOS women were obese and 44.5% of PCOS women were overweight.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…There is a strong correlation between PCOS with obesity, especially central obesity, as reported by previously conducted studies [26,27]. Similar results were reported by Abdelazim et al [28], who found that 35.5% of PCOS women were obese and 44.5% of PCOS women were overweight.…”
Section: Discussionsupporting
confidence: 87%
“…In present study, serum testosterone, free testosterone, and LH:FSH ratio were significantly higher in women with PCOS having higher BMI (p value = 0.041). Hyperandrogenism was also reported with PCOS by Nath et al ( 2019) and Hamed et al (2022) [12,27]. In the study by Hamed et al [27], serum testosterone levels were also positively correlated with estradiol (r=0.372, p<0.0001) in cases with higher BMI.…”
Section: Metabolic Parameters In Pcosmentioning
confidence: 53%
See 3 more Smart Citations